If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -6(2x + -3) + 1 = 3 + 7(5 + -1x) Reorder the terms: 4 + -6(-3 + 2x) + 1 = 3 + 7(5 + -1x) 4 + (-3 * -6 + 2x * -6) + 1 = 3 + 7(5 + -1x) 4 + (18 + -12x) + 1 = 3 + 7(5 + -1x) Reorder the terms: 4 + 18 + 1 + -12x = 3 + 7(5 + -1x) Combine like terms: 4 + 18 = 22 22 + 1 + -12x = 3 + 7(5 + -1x) Combine like terms: 22 + 1 = 23 23 + -12x = 3 + 7(5 + -1x) 23 + -12x = 3 + (5 * 7 + -1x * 7) 23 + -12x = 3 + (35 + -7x) Combine like terms: 3 + 35 = 38 23 + -12x = 38 + -7x Solving 23 + -12x = 38 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 23 + -12x + 7x = 38 + -7x + 7x Combine like terms: -12x + 7x = -5x 23 + -5x = 38 + -7x + 7x Combine like terms: -7x + 7x = 0 23 + -5x = 38 + 0 23 + -5x = 38 Add '-23' to each side of the equation. 23 + -23 + -5x = 38 + -23 Combine like terms: 23 + -23 = 0 0 + -5x = 38 + -23 -5x = 38 + -23 Combine like terms: 38 + -23 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| 2-8m=14-3+8m | | t^2-24=2t | | k^2-20k-35=0 | | g(x)=x+7(2x)2x+14 | | 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 | | 35+x+2x=42+9x | | 50-8x-3=15 | | 50-8x-3=16 | | 50-8x-3=18 |